Meningkatkan Motivasi dan Keterampilan Menyimak Siswa SMA melalui Pembelajaran Listening Berbasis Multimedia Interaktif - Marshanda, Marshanda; Setiawan, Muhammad Dicky; Ramadhani, Raysha; Rani, Rani; Rahmawati, Siti; Putri, Fara Suseno; Putri, Rica Amelia; Musyaffa, Roshim Ahmad; Fahlevi, Fauzan Reza; Palmatiwi, Dyah Hanum; Ikrimah, Ikrimah; Nadia, Aghnia Assifa; Nadia, Nadia; Syahid, Abdul (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aimed to enhance senior high school students’ listening comprehension and learning motivation through multimedia-based activities using English songs and a short film. The program was motivated by limited exposure to authentic listening input and the lack of integrated multimedia approaches in English classrooms. The activity was conducted in the form of a workshop involving 35 students through guided listening tasks using a pop song, a short film, and a planned Quizizz activity that could not be implemented due to time constraints. Data were collected through classroom observations, students’ worksheets, and informal feedback. The results indicate high levels of student engagement, enthusiasm, and collaborative interaction during the learning process. Worksheet analysis shows improvement in vocabulary recognition, understanding of key information, and interpretation of audiovisual cues. These findings suggest that multimedia-based listening instruction is effective in improving students’ motivation and listening comprehension and should be sustainably integrated into English language teaching practices.